Effects of creatine monohydrate on endurance performance in a trained population: a systematic review and meta-analysis - Fernández-Landa, J.; Santibañez-Gutierrez, A.; Todorovic, N.; Stajer, V.; Ostojic, S. M. (Sports Medicine, 2023)
Background: There is robust evidence that creatine monohydrate supplementation can enhance short-term high-intensity exercise in athletes. However, the effect of creatine monohydrate supplementation on aerobic performance and its role during aerobic activities is still controversial. Objective: The purpose of this systematic review and meta-analysis was to evaluate the supplementation effects of creatine monohydrate on endurance performance in a trained population. Methods: The search strategy in this systematic review and meta-analysis was designed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and PubMed/MEDLINE, Web of Science, and Scopus databases were explored from inception until 19 May, 2022. Only human experimental trials, controlled with a placebo group, evaluating the effects of creatine monohydrate supplementation on endurance performance in a trained population were analyzed in this systematic review and meta-analysis. The methodological quality of included studies was evaluated using the Physiotherapy Evidence Database (PEDro) scale. Results: A total of 13 studies satisfied all the eligibility criteria and were included in this systematic review and meta-analysis. The results for the pooled meta-analysis showed a non-significant change in endurance performance after creatine monohydrate supplementation in a trained population (p = 0.47), with a trivial negative effect (pooled standardized mean difference = - 0.07 [95% confidence interval - 0.32 to 0.18]; I2 = 34.75%). Further, after excluding the studies not evenly distributed around the base of the funnel plot, the results were similar (pooled standardized mean difference = - 0.07 [95% confidence interval - 0.27 to 0.13]; I2 = 0%; p = 0.49). Conclusions: Creatine monohydrate supplementation was shown to be ineffective on endurance performance in a trained population.